The 30-day Alzheimer's solution : the definitive food and lifestyle guide to preventing cognitive decline - Sherzai, Dean; Sherzai, Ayesha (San Francisco : HarperOne, 2021)
"The first 30-Day nutrition plan for preventing and reversing the symptoms of Alzheimer's disease, dementia, and cognitive decline from Co-Directors of the Alzheimer's Prevention Program at Loma Linda University Medical Center"--.
Includes bibliographical references and index.
Keywords: Alzheimer's disease -- Prevention -- Popular works; Alzheimer's disease -- Diet therapy -- Popular works; Cooking -- Popular works